A importância dos materiais manipuláveis para o desenvolvimento do sentido do número num grupo do pré-escolar - Machado, Ricardo (2020)
Nowadays, knowing and putting into action knowledge about numbers and operations is very important. However, this knowledge must be related to a global understanding of numbers and operations, which arises in various contexts. In this way, we can say that developing the meaning of numbers has never been more prominent than now. Thus, the development of this competence must be worked from the earliest years, particularly in pre-school education. On the other hand, as we work with children the use of manipulative material assumes as an essential and fundamental element when it is intended to promote learning with understanding, since it allows, in a playful, appealing and motivating way to children appropriate mathematical knowledge and develop (mathematical) abilities and competencies. In this way, it was felt the need to elaborate mathematical tasks that promoted the use of manipulative materials with the purpose of motivating and involving the children in the mathematical activity. This research is part of an interpretative paradigm, in which we intend to understand the role of manipulative materials in the development of number sense in a group of children of pre-school education, through the forms of action of the participants involved. This work was developed through an action-research project, having as participants a group of 23 children between the ages of 3 and 6 years old. As data collection instruments we used the observation, the educator/researcher’s diary, informal conversations and documents. Regarding the results, it was evident the interest of the group in performing all the tasks. The group of children was motivated and involved in the accomplishment of these tasks, achieving mathematic knowledge, namely regarding the development of number sense.